Identifikasi Bakteri Salmonella sp Pada Gado-Gado Yang Dijual Area Kampus Universitas Halu Oleo Tahun 2021 - Anita; Ramadhan Tosepu; Fifi Nirmala G (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2022)
Gado-gado is a dish made from a variety of vegetables and uses peanut sauce to add flavor to the vegetables. The main problem with fast food like gado-gado is safety due to the lack of attention to the hygienic aspects of food handlers. During the preparation and processing of gado-gado that does not meet the requirements, such as undercooked boiling and poor sanitary conditions, it can lead to cross-contamination of gado-gado. This study aims to identify Salmonella sp bacteria in gado-gado sold in the Halu Oleo University campus area in 2021. This study uses a descriptive type of research with a sampling technique using total sampling. The results of this study showed that from 10 samples of gado-gado there were 5 (50%) samples of gado-gado that were positive for Salmonella sp bacteria and 5 (50%) samples of gado-gado were negative for Salmonella sp. The results of personal hygiene of food handlers who have bad personal hygiene are 6 or (60%) food stalls and food stalls that have good personal hygiene are 4 or (40%) food stalls. The results of the sanitation of the food stalls did not meet the requirements with a score of <65 as many as 9 or (90%) stalls and there were 1 or (10%) stalls that met the stall requirements with a score of ≥65. Studies have concluded that a hodgepodge convered by Salmonella sp is home to 5 samples of the hodgepositve that positive bacteria Salmonella sp and personal hygiene and poor decorator at 6 and sanitation of unqualified food stalls as much as 9.